Systematic kinetic analysis of mitotic dis- and reassembly of the nuclear pore in living cells - Dultz, Elisa (The Rockefeller University Press, 2008)
During mitosis in higher eukaryotes, nuclear pore complexes (NPCs) disassemble in prophase and are rebuilt in anaphase and telophase. NPC formation is hypothesized to occur by the interaction of mitotically stable subcomplexes that form defined structural intermediates. To determine the sequence of events that lead to breakdown and reformation of functional NPCs during mitosis, we present here our quantitative assay based on confocal time-lapse microscopy of single dividing cells. We use this assay to systematically investigate the kinetics of dis- and reassembly for eight nucleoporin subcomplexes relative to nuclear transport in NRK cells, linking the assembly state of the NPC with its function. Our data establish that NPC assembly is an ordered stepwise process that leads to import function already in a partially assembled state. We furthermore find that nucleoporin dissociation does not occur in the reverse order from binding during assembly, which may indicate a distinct mechanism.